Anxiety and determinants among patients with chronic diseases during pandemic of emerging infectious diseases: a moderated mediation analysis - Wang, Yuxiao; Li, Sitian; Zheng, Haiting; Zhang, Yaodan; Zhang, Jingru; La, Yuanyuan; Xie, Jun; Li, Jiantao; He, Lu (Frontiers in Public Health, 2025)
BackgroundThis study aims to investigate the anxiety levels and associated influencing factors among patients with chronic diseases during the pandemic of emerging and sudden infectious diseases. The findings are intended to provide a theoretical foundation for developing targeted psychological intervention strategies, thereby enhancing the mental health support for chronic disease patients in times of public health crises.MethodsThis study was conducted in Shanxi Province between December 2022 and January 2023, utilizing a cross-sectional research design with a total sample size of 40,302 participants. Chi-square tests were employed to assess differences across groups in sociodemographic characteristics, prevalence of chronic diseases, vaccination status, self-perceived symptoms, availability of essential supplies, and anxiety levels. Additionally, a moderated mediation model was applied to examine the potential pathways through which these variables influence anxiety. All statistical analyses were carried out using R software.ResultsIncreasing the number of emerging and sudden infectious diseases vaccination doses negatively predicted anxiety (β = −0.0249, 95%CI = [−0.0393, −0.0106]), a relationship partially mediated by self-perceived symptoms (effect = 0.0102, SE = 0.002, 95%CI = [0.0062, 0.0142]). Personal material reserves and residential GDP significantly moderated anxiety (β = −0.035, 95%CI = [0.0426, −0.0273]; β = 0.033, 95%CI = [0.0127, 0.0533]). The effect of self-perceived symptoms on anxiety was greater in areas with lower GDP and among patients with chronic diseases with poorer material reserves.ConclusionThis study highlights the critical role of vaccination in reducing anxiety during public health emergencies, particularly among chronic disease patients, and identifies key factors such as self-perceived symptoms, material reserves, and local GDP. Strengthening vaccination coverage and securing essential supplies for high-risk groups are vital to safeguarding their mental health in such crises. These findings offer both theoretical and practical insights for addressing post-outbreak anxiety.